(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
The narrator of the Inamoramento de Orlando often represents himself speaking to his audience, and the descriptions of the audience that we can extract from those representations change throughout the poema. This contribution shows how women get included in the audience pictured by the speaker starting from the second half of the second book: this innovation is related to an actual change in the social composition of the Ferrara’s court (notably with the arrival of Eleonora d’Aragona in 1473) and it affects the moral and political message of Boiardo’s work. A comparison with Ariosto’s Orlando furioso allows a better understanding of the uniqueness of the Inamoramento’s approach to female audience representation.